LABORATORY FINDING AND CLINICAL MANIFESTATION AFFECTING THE LENGTH OF STAY OF HOSPITALIZATION ON CHILDREN WITH DENGUE HEMORRHAGIC FEVER - Yanuarita Tursinawati; Galuh Ramaningrum; Indah Aprilia D.M (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Dengue Hemorrhagic Fever (DHF) was a disease caused by dengue virus infection with high morbidity.Most DHF patients required hospitalization care. The length of stay of hospitalization increased the cost and became burden of the patient's family. Length of stay (LOS) was an indicator to assess the quality of health services. The purpose of this research was to analyze the factors related the LOS of pediatric patients with DHF in Tugurejo hospital, Semarang. This was an observational study with cross sectional analytic. Total sample was 137 children with DHF who was hospitalized in Tugurejo hospital, Semarangduring the period of September 1st  2015- August 31 2016. The sample data was obtained from medicalrecords that used purposive-sampling techniques. Data analysis used chi-square test with < 0.05 significance level and 95% confidence intervals. The analysis showed that platelet counts (p = 0.000), hematocrit (p = 0.000), hemoglobin (p = 0.000), complications (p = 0.000), the degree of fever (p = 0.027) and duration of fever before hospitalization (p = 0.000) significantly related to LOS of pediatric patients with DHF and there was no significant related of leukocyte count (p = 0.374) to LOS of pediatricpatients with DHF. Prolonged LOS was associated with laboratory finding and clinical manifestation. By knowing these factors, practitioner could provide a more effective and efficient treatment to patients with DHF to shorten the LOS. Keyword : laboratory finding, clinical manifestation, length of stay, Dengue Hemorrhagic Fever